The adventures of Ma & Pa Kettle. Volume 2. [videorecording (DVD)] - Main, Marjorie, 1890-1975; Kilbride, Percy, 1888-1964 (Franchise collection., 2004)
"America's favorite country couple are back together again in a brand-new collection featuring four all-time favorites."